2018
DOI: 10.3390/su10041155
|View full text |Cite
|
Sign up to set email alerts
|

Exercise on Transdisciplinarity: Lessons from a Field-Based Course on Rural Sustainability in an Aging Society

Abstract: Sustainability science emerged as a new academic field to address complex sustainability challenges. To train sustainability experts, sustainability science programs and sustainability-focused courses are offered in higher education, especially at the graduate level. Given the diverse topics and the complex structures of sustainability challenges, what are the required knowledge and skills needed for sustainability experts? Although the earlier literature identified key features and competencies, empirical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The activation of students' learning process is promoted by the providing of cognitive tasks on interdisciplinary nature, what stimulates creativity, develops cognitive activity, forms systemic thinking and further help to solve non-standard issues in different areas of professional and social practice [11]. Learning effectiveness on the basis of interdisciplinary connections is usually achieved by innovative activity in its goals, content, forms of organization of the educational process, by developing students' self-organization, forecasting and modeling skills.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of students' learning process is promoted by the providing of cognitive tasks on interdisciplinary nature, what stimulates creativity, develops cognitive activity, forms systemic thinking and further help to solve non-standard issues in different areas of professional and social practice [11]. Learning effectiveness on the basis of interdisciplinary connections is usually achieved by innovative activity in its goals, content, forms of organization of the educational process, by developing students' self-organization, forecasting and modeling skills.…”
Section: Resultsmentioning
confidence: 99%
“…Realistically, each stakeholder group has different interests, and they barely find common grounds spontaneously just by sitting together. There must be a facilitator who has the ability to be empathetic and accommodate each stakeholder’s point of view (Kudo et al , 2018). To train researchers with such facilitation skills for transdisciplinary approaches, sustainability-focused educational programs in higher education must offer a designed learning space where students can experience the actual co-production of socially robust knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama and Matsumura [18] reported that students improved their fundamental competencies as professionals after experiencing FW in rural areas. Moreover, Kudo et al [19] found that communicating with students from different countries and diverse disciplines who are working on the same theme promotes independence, cooperation, and indepth understanding of their field of study. In addition, FW enables students to gain a sense of responsibility as members of the community.…”
Section: Theoretical Backgroundmentioning
confidence: 99%